Stock Repurchase in Turkey: Event Study Application - Abraş, Belgin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Share repurchases have become substitute for cash dividends. In a share repurchase program, a corporation buys back its own shares. It has been a common practice in the developed markets. However, the strict regulations in Turkey laws had not allowed the corporations to repurchase their shares until 2009. In 2011, the regulatory body in Turkey, Capital Markets Board has made it possible for all corporations listed on Borsa Istanbul Stock Market to carry out share repurchase programs. There are many motivations for share repurchases, but the undervaluation signaling is the driving motivation for managers to implement a share repurchase program. Signaling has two kinds of use by managers; it indicates an undervaluation for the current stock price in the market and sends a positive signal to correct for this undervaluation. The purpose of this thesis is to analyze whether share repurchase announcements has an effect on corporation’s stock prices and to test the semi-strong efficiency of Borsa Istanbul (BIST) by using the traditional event study methodology. The data contains 19 non-financial corporations and 27 observations. The results show that there is a positive market reaction to share repurchase announcements and the driving motivation is the undervaluation signal. However, the results also show that the BIST stock market is not semi-strong efficient and for the case of share repurchases, a market overreaction is observed. Keywords: Share repurchase, Borsa Istanbul, Event Study, Abnormal Return, Signaling, Undervaluation

ÖZ: Hisse geri alımları, nakit temettünün yerini almış ve ayrıca şirketler için ödeme yöntemlerinin değiştirilmesinde önemli bir rol oynamaktadır. Hisse geri alımı, temel olarak şirketin piyasadan kendi hisselerini geri almasıdır. Küresel pazarlarda yaygın bir uygulama olarak kullanılmaktadır. Ancak, Türkiye yasalarındaki sıkı düzenlemeler, şirketlerin 2009 yılına kadar kendi hisselerini piyasadan geri almalarına izin vermemekteydi. 2011'de Sermaye Piyasası Kurulu'nun açıklanması ile Borsa İstanbul Menkul Kıymetler’de listelenmiş tüm şirketler hisse geri alımı yapabilecekti. Hisse geri alımları için birçok motivasyon kaynağı bulunmaktadır. Ancak piayasaya mesaj verilmesi yaklaşımı yöneticiler için hisse geri alım programlarını gerçekleştirmeleri için önemli bir motivasyon kaynağı olmuştur. Piyasaya mesaj verme yöneticiler tarafından iki türlü olarak kullanılmaktadır; hisse senedinin değer düşüklüğüne işaret etmekte olup ayrıca yatırımcılara pozitif sinyaller göndererek hisse fiyatında artışa sebep olmaktadır. Bu tezin amacı, hisse senedi geri alım duyurularının şirketilerin hisse fiyatları üzerinde bir etkisi olup olmadığını analiz etmek ve aynı zamanda olay incelemesi metodolojisini kullanarak Borsa İstanbul'un (BIST) yarı güçlü etkinliğini test etmektir. Çalışmada 19 finansal olmayan şireket ve 27 adet gözlem kullanılmıştır. Sonuçlar, hisse geri alım duyurularının, şirket hisseleri üzerinde anormal getiri sağladığına ve BIST'in yarı-güçlü verimlilikte etkili olmadığını ortaya koymaktadır. Anahtar Kelimeler: Hisse geri alımı,Borsa Istanbul, Olay Çalışması, Anormal Getiri, Eksik Değerleme
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2019. Supervisor: Prof. Dr. Cahit Adaoğlu.
Keywords: Banking and Finance; Banking and Finance--Turkey; Stock Repurchasing--Turkey; Share repurchase; Borsa Istanbul; Event Study; Abnormal Return; Signaling; Undervaluation